Hypnosis for Pain Alleviation: Placebo or Nocebo? - Dias Rima Sutiono; Jeremy Putra Gunawan; Astrella Devina; Wibi Sindjaja; Jesslyn Pavita (Cermin Dunia Kedokteran, 2019)
The use of hypnosis to alleviate pain had started to gain recognition. In the assessed papers, application of hypnosis has included childbirth, surgeries, and chronic pain. In childbirth, the use of self-hypnosis can reduce the use of analgesics from 78% to 45% of cases. The satisfaction of hypnobirthing—birth using hypnosis—reaches 96%. Hypnosis can decrease the use of anesthesia drugs during surgery, promotes healing, decreases bleeding and hospital stay. Hypnosis can alleviate pain and reduce the use of over the counter painkillers; also showed benefits for non-cardiac chest pain relief while also reduces medication. Currently, hypnosis had been the most prominent application for labour pain relief. There is a demand for more studies of bioinformatics and neuroscience.Penggunaan hipnosis untuk mengurangi rasa sakit sudah mulai mendapat pengakuan. Banyak pustaka menjelaskan penerapan hipnosis pada proses melahirkan, operasi, dan nyeri kronis. Pada proses melahirkan, self-hypnosis dapat mengurangi penggunaan analgesik dari 78% menjadi 45% kasus. Kepuasan hypnobirthing – kelahiran menggunakan hipnosis - mencapai 96%. Hipnosis dapat mengurangi penggunaan obat anestesi, mempromosikan penyembuhan, mengurangi perdarahan dan lama rawat di rumah sakit pasca-operasi. Hipnosis bisa mengurangi penggunaan obat penghilang nyeri; juga menunjukkan manfaat untuk penderita nyeri dada non-jantung selain mengurangi konsumsi obat. Saat ini, aplikasi hipnosis yang paling menonjol untuk nyeri persalinan. Diperlukan studi bioinformatika dan neuroscience lebih lanjut.